Policy evaluation for a complex world: Practical methods and reflections from the UK Centre for the Evaluation of Complexity across the Nexus. (January 2021) - Barbrook-Johnson, Pete; Castellani, Brian; Hills, Dione; Penn, Alexandra; Gilbert, Nigel
The value of complexity science and related approaches in policy evaluation have been widely discussed over the last 20 years, not least in this journal. We are now at a crossroads; this Special Issue argues that the use of complexity science in evaluation could deepen and broaden rendering evaluations more practical and rigorous. The risk is that the drive to better evaluate policies from a complexity perspective could falter. This special issue is the culmination of 4 years' work at this crossroads in the UK Centre for the Evaluation of Complexity Across the Nexus. It includes two papers which consider the cultural and organisational operating context for the use of complexity in evaluation and four methodological papers on developments and applications. Together, with a strong input from practitioners, these papers aim to make complexity actionable and expand the use of complexity ideas in evaluation and policy practice.